Maternal factors are important predictors for surgical site infection following cesarean section in Northwest Ethiopian - Oumer Ali; Dawit Kassahun; Bayew Kelkay Rade; Asmamaw Atnafu (Elsevier, 2022)
Background: Surgical site infection (SSI) is a common surgical complication following cesarean section(C/S) that increases maternal morbidity, duration of hospital stay and the cost of treatment. It is more prevalent in Sub-Saharan Countries, including Ethiopia. As the best of authors knowledge, limited representative data in the study setting. Therefore, this study aimed to figure out the magnitude and factors associated with surgical site infection. Methods: Client record review was employed from 818 mothers who underwent cesarean section in University of Gondar comprehensive specialized hospital from January 1, 2018 to January 1, 2019. Charts were selected using systematic random sampling technique. Data were entered into EPI info version 7.0 and then exported to SPSS version 20 for analysis. Descriptive statistics, bivariate, and multivariable logistic regression were applied to summarize the data. A p-value < 0.05 was a cut-off point to declare statistical significance. Results: This study revealed that the prevalence of SSI was 12.2% with 95% CI (9.96-14.44). Chorioamnionitis [AOR = 6.46, 95% CI (1.82-22.71)], diabetes mellitus [AOR = 6.02, 95% CI (1.69-21.36)], rupture of membrane more than 12 h before cesarean section [AOR = 2.94, 95% CI (1.52-5.67)], meconium-stained amniotic fluid [AOR = 2.43, 95% CI (1.23-4.81)] and anemia [AOR = 3.44, 95% CI (1.56-7.56)] were significantly associated factors with SSI following cesarean delivery. Conclusion: The magnitude of SSI was high, and maternal related (medical and obstetrical) factors were found significant association with it. Improvement of early identification of risk factors, and prompt treatment/control of obstetrical and medical complications are the recommendations.